2022
DOI: 10.1007/s00005-022-00648-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Lactoferrin Reduces Inflammation and Increases Fluoroquinolone Penetration to Primary Granulomas During Mycobacterial Infection of C57Bl/6 Mice

Abstract: Infection with Mycobacterium tuberculosis ( Mtb ) results in the primary formation of a densely packed inflammatory foci that limits entry of therapeutic agents into pulmonary sites where organisms reside. No current therapeutic regimens exist that modulate host immune responses to permit increased drug penetration to regions of pathological damage during tuberculosis disease. Lactoferrin is a natural iron-binding protein previously demonstrated to modulate inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…In a mouse model, inflammatory foci in lungs of Mycobacterium tuberculosis -infected animals hamper the penetration of therapeutics to infected sites and bacteria destruction. Oral recombinant human LF (rhLF) was used in C57BL mice as an adjuvant therapy with ofloxacin fluoroquinolone [ 91 ]. Histological analysis revealed that treatment with LF enabled penetration of the antibiotic to the pathologic sites populated with activated macrophages.…”
Section: Lactoferrin As Supportive Therapy In Antibiotic Treatmentmentioning
confidence: 99%
“…In a mouse model, inflammatory foci in lungs of Mycobacterium tuberculosis -infected animals hamper the penetration of therapeutics to infected sites and bacteria destruction. Oral recombinant human LF (rhLF) was used in C57BL mice as an adjuvant therapy with ofloxacin fluoroquinolone [ 91 ]. Histological analysis revealed that treatment with LF enabled penetration of the antibiotic to the pathologic sites populated with activated macrophages.…”
Section: Lactoferrin As Supportive Therapy In Antibiotic Treatmentmentioning
confidence: 99%
“…Therefore, inhibiting the cytokine storm may be a prophylactic and therapeutic approach toward combating COVID-19 infection (Zimecki et al, 2021).In the study of pulmonary acute respiratory distress syndrome (ARDS) in granulomatous inflammation model (Mrityunjaya et al, 2020), it was found that LF can reduce or eliminate cytokine excess and pulmonary pathological features caused by Mycobacterium tuberculosis (Welsh et al, 2011;Hwang et al, 2017). In addition, LF was also able to diminish hyperacute immunopathology developed after the administration of isolated surface mycolic acid components (Nguyen et al, 2021(Nguyen et al, , 2022. LF significantly induced the expression of the antiviral immune response genes and partially inhibited SARS-CoV-2 infection and replication in Caco-2 intestinal epithelial cells to protect against SARS-CoV-2 infection in vitro (Salaris et al, 2021).…”
Section: Emerging Topicsmentioning
confidence: 99%